IN VITRO MEROPENEM SUSCEPTIBILITY INDUCED BY PH ALTERATION IN METALLO-BETA-LACTAMASE POSITIVE PSEUDOMONAS AERUGINOSA - Chakraborty, Urmita; Roychowdhury, Rittwika; Chatterjee, Debasmita; Das, Satadal (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The increasing emergence of metallo-beta-lactamase (MÎ²L) producing Gram-negative bacteria such as Pseudomonas aeruginosa pose a serious public health concern including in the treatment of urinary tract infection (UTI). This study was aimed to explore the combined effect of in vitro pH alteration and antibiotic on the bacterial growth as a potential therapeutic approach against the drug resistant P. aeruginosa. Methods: Ten MÎ²L producing P. aeruginosa isolates from the patients suffering from UTI were included. Bacteria were inoculated with or without meropenem in media with varied pH range from 5 to 10. The variation of bacterial growth was determined by measuring the changes of optical density at 620 nm and colony forming unit counts/ml. Result: The growth of bacteria was reduced both at very high and lower pH ranges. However, the growth was further reduced significantly with the addition of meropenem at these extreme pH conditions. Conclusion: Alteration of pH especially at lower range of the medium might has changed the efficacy of MÎ²L and thus helped the antibiotic meropenem to act on the bacteria, which was resistant toward the same at neutral pH. Combined effect of antibiotic and pH modulation of biological fluid like urine should be explored for an effective alternative therapeutic approach against the drug-resistant bacteria. Keywords: Metallo-beta-lactamase, urinary tract infection, Pseudomonas aeruginosa, pH.